EFFECT OF WORKING CAPITAL MANAGEMENT AND LEVERAGE ON COMPANY VALUE WITH PROFITABILITY AS MODERATING VARIABLES: Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange - Kasim, Shahreen; Sumatrani Saragih, Majied; Saifannur, Andri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study aims to determine how the influence of working capital management and leverage on firm value with profitability as a moderating variable. The research method used is quantitative data method. 1) Working Capital Management variable has a positive and significant effect on Firm Value. 2) Leverage variable has no significant effect on firm value. 3) Working Capital Management and Leverage variables have no simultaneous significant effect on Firm Value. 4)Profitability variable is a moderator variable that affects the relationship between Working Capital Management and Firm Value. 5) Profitability variable is not a moderator variable that can moderate the relationship between Leverage and Firm Value.Company value can be used as the basis for making investment decisions because this aspect measures the ability of the company's assets to generate a return on investment made in the company's asset instruments.